2020
DOI: 10.1038/s41598-020-65521-z
|View full text |Cite
|
Sign up to set email alerts
|

Near IR responsive targeted integrated lipid polymer nanoconstruct for enhanced magnolol cytotoxicity in breast cancer

Abstract: Advances in cancer nanotechnology aim at improving specificity and effectiveness for tumor treatment. Amalgamation of different treatment modalities is expected to provide better cancer combating. Herein, We developed a long circulating nanocarrier comprising trastuzumab (TZB) surface modified polylactic-co-glycolic acid (pLGA) nanoparticles (nps) co-encapsulating magnolol (Mag) and gold nanoparticles (GNPs). A modified single step nanoprecipitation method was adopted ensuring particle coating with D-α-tocophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The results showed that the entrapment efficiency of MAG was over 81%, which improved the cytotoxicity of MAG to breast cancer cells and provided photothermal effect for multifunctional therapy of breast cancer cells. The encapsulated photothermal material GNPs enables the nano‐carrier to give near‐infrared photothermal response, which improves the cytotoxicity of drugs and enhances the specificity to cancer cells 38 . We thus hypothesized that targeting antigen present cells modification of IsdB 137‐361 ‐PEI‐PLGA nanoparticles might have a better immune effect, but this needs to be verified by subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the entrapment efficiency of MAG was over 81%, which improved the cytotoxicity of MAG to breast cancer cells and provided photothermal effect for multifunctional therapy of breast cancer cells. The encapsulated photothermal material GNPs enables the nano‐carrier to give near‐infrared photothermal response, which improves the cytotoxicity of drugs and enhances the specificity to cancer cells 38 . We thus hypothesized that targeting antigen present cells modification of IsdB 137‐361 ‐PEI‐PLGA nanoparticles might have a better immune effect, but this needs to be verified by subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…There have many reports about the use of hybrid NPs in cancer detection and treatment. There are some hybrid NPs for clinical diagnosis of cancer, including hybrid magnetic silicon dioxide NPs [ 137 ] and hybrid supermagnetic iron oxide NPs (SPIONS) [ 138 , 139 , 140 , 141 ]. Some hybrid NPs are used for cancer treatment, such as lipid coated polymers [ 142 , 143 ] and hybrid NPs coupled with genes [ 144 ].…”
Section: The Nanocarriers For Cancer Targeting Therapymentioning
confidence: 99%
“…Therefore, combining the advantages of the two to construct hybrid nanocarriers can not only improve the targeting ability of nanocarriers, but also increase the anti-tumor effect of drugs. For example, Elhabak’ team developed a trastuzumab (TZB) surface modified poly(lactic-co-glycolic) acid (PLGA), circulating NPs that co-encapsulated magnolol (Mag) and gold NPs [ 139 ]. The optimized NPs have small particle sizes and high encapsulation efficiency.…”
Section: The Nanocarriers For Cancer Targeting Therapymentioning
confidence: 99%
“…[66] Together with magnolol and obovatol as analgesics, honokiol has been prescribed in conventional treatments to address depression and anxiety issues. [67] Multiple studies have discovered that honokiol has the capacity to destroy tumour cells in various types of cancer. [68][69][70]…”
Section: Lignansmentioning
confidence: 99%